Structure of Plant Cell Walls: XI. GLUCURONOARABINOXYLAN, A SECOND HEMICELLULOSE IN THE PRIMARY CELL WALLS OF SUSPENSION-CULTURED SYCAMORE CELLS - Darvill, Janet E. (1980)
The isolation, purification, and partial characterization of a glucuronoarabinoxylan, a previously unobserved component of the primary cell walls of dicotyledonous plants, are described. The glucuronoarabinoxylan constitutes approximately 5% of the primary walls of suspension-cultured sycamore cells. This glucuronoarabinoxylan possesses many of the structural characteristics of analogous polysaccharides that have been isolated from the primary and secondary cell walls of monocots as well as from the secondary cell walls of dicots. The glucuronoarabinoxylan of primary dicot cell walls has a linear β-1,4-linked d-xylopyranosyl backbone with both neutral and acidic sidechains attached at intervals along its length. The acidic sidechains are terminated with glucuronosyl or 4-O-methyl glucuronosyl residues, whereas the neutral sidechains are composed of arabinosyl and/or xylosyl residues.